Detection and expression analysis of tet(B) in Streptococcus oralis. Issue 1 (1st January 2019) - Arredondo, Alexandre; Àlvarez, Gerard; Nart, José; Mor, Carolina; Blanc, Vanessa; León, Rubén
ABSTRACT: Tetracycline resistance can be achieved through tet genes, which code for efflux pumps, ribosomal protection proteins and inactivation enzymes. Some of these genes have only been described in either Gram-positive or Gram-negative bacteria. This is the case of tet (B), which codes for an efflux pump and, so far, had only been found in Gram-negative bacteria. In this study, tet (B) was detected in two clinical Streptococcus oralis strains isolated from the gingival sulci of two subjects. In both cases, the gene was completely sequenced, yielding 100% shared identity and coverage with other previously published sequences of tet (B). Moreover, we studied the expression of tet (B) using RT-qPCR in the isolates grown with and without tetracycline, detecting constitutive expression in only one of the isolates, with no signs of expression in the other one. This is the first time that the presence and expression of the tet (B) gene has been confirmed in Gram-positive bacteria, which highlights the potential of the genus Streptococcus to become a reservoir and a disseminator of antibiotic resistance genes in an environment so prone to horizontal gene transfer as is the oral biofilm.